Designing and Constructing Skill Performance Tests for Futsal Female Players - Alzuhairy, Rabee Khalaf Jameel (Journal of Physical Education, 2021)
The research aimed at designing and constructing a number of tests for skill performance endurance for female futsal players as well as identifying standard criteria for these tests. The researcher used the descriptive method on (105) female futsal players from the northern region of Iraq including clubs (Tenahi, Fetat Arbil, Shekhan, Jehan, Gaz Al Shemal, Afrodate, Serwan, Newi). The data was concluded and treated using SPSS to concluded (6 – 8) criteria for these tests under study.